2017
DOI: 10.1016/j.redox.2017.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Protein aggregation into insoluble deposits protects from oxidative stress

Abstract: Protein misfolding and aggregation have been associated with the onset of neurodegenerative disorders. Recent studies demonstrate that the aggregation process can result in a high diversity of protein conformational states, however the identity of the specific species responsible for the cellular damage is still unclear. Here, we use yeast as a model to systematically analyse the intracellular effect of expressing 21 variants of the amyloid-ß-peptide, engineered to cover a continuous range of intrinsic aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 70 publications
(97 reference statements)
0
18
0
2
Order By: Relevance
“…Mechanistic studies were performed and suggest that R. genevieri (poly)phenolics led FUS to be trapped into insoluble intracellular structures thereby reducing its pathological activity. This is a well-known route of cellular protection against the toxic effect of several oligomerization-prone proteins described for several diseases [ 40 ]. It remains to identify the major molecular players in this process and to evaluate whether this mechanism is conserved in higher eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic studies were performed and suggest that R. genevieri (poly)phenolics led FUS to be trapped into insoluble intracellular structures thereby reducing its pathological activity. This is a well-known route of cellular protection against the toxic effect of several oligomerization-prone proteins described for several diseases [ 40 ]. It remains to identify the major molecular players in this process and to evaluate whether this mechanism is conserved in higher eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Redox signalling-dependent protein oxidation could, therefore, be a facilitator of aggregation and actually partake in the proteotoxic stress response. In support of this, it was shown that promoting the formation of large insoluble aggregates is protective against amyloid-induced ROS production [112].…”
Section: Cysteine Oxidation-driven Protein Aggregation In Diseasementioning
confidence: 92%
“…have been shown to favor protein aggregation, presumably by lowering the energy barriers separating native from misfolded conformations (18)(19)(20)(21). Although, in some cases, nonamyloid protein aggregation can induce cell death (22,23), protein aggregation may also be beneficial to cells as long as sequestration of aggregates in specific cell sites prevents toxicity (24). Indeed, nonamyloid protein aggregates may be asymmetrically inherited by daughter cells (25), dissolved by chaperones (12,26), or digested by proteases (27) or autophagy (28,29).…”
Section: Significancementioning
confidence: 99%